2022
DOI: 10.1093/cid/ciac548
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Severe Acute Respiratory Syndrome Coronavirus 2 Infection With accumulation of mutations in a patient with poorly controlled Human Immunodeficiency Virus infection

Abstract: A 22-year-old woman with uncontrolled advanced human immunodeficiency virus (HIV) infection was persistently infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) beta variant for 9 months, the virus accumulating >20 additional mutations. Antiretroviral therapy suppressed HIV and cleared SARS-CoV-2 within 6 to 9 weeks. Increased vigilance is warranted to benefit affected individuals and prevent the emergence of novel SARS-CoV-2 variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…The identification of risk factors for a reduced response to SARS-CoV-2 vaccines in PLWH is important as it will help to improve vaccination strategies in PLWH. A good understanding of vaccination response in PLWH is even more important now that variants of concern (VOCs) continue to arise and partially escape vaccine-induced immunity [ 15 ], especially considering the possibility of VOCs arising in PLWH unable to clear the virus due to an untreated HIV infection [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of risk factors for a reduced response to SARS-CoV-2 vaccines in PLWH is important as it will help to improve vaccination strategies in PLWH. A good understanding of vaccination response in PLWH is even more important now that variants of concern (VOCs) continue to arise and partially escape vaccine-induced immunity [ 15 ], especially considering the possibility of VOCs arising in PLWH unable to clear the virus due to an untreated HIV infection [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also has increased environmental stability, suggesting that transmission via the airborne route may be more frequent 32,33 . It may also replicate faster in human respiratory epithelial cells, 34 and this could lead to more rapid accumulation of mutations and intrahost evolution in chronic infections 35,36 . Recently, Lai et al found that viral RNA shedding of exhaled breath aerosols in patients with Alpha, Delta, and Omicron variants increased, compared with previous variants of concerns, but there was no significant difference in peak RNA shedding between Delta and Omicron variants 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In numerous studies, it was discovered that Africans have higher nucleotide and haplotype diversity than non-Africans [ 5 , 28 , 29 , 30 ]. In another study, ACE2 receptors are presented with some different nonsynonymous mutations in African populations which were identified as signatures of selection affecting variation at regulatory regions related to ACE2 expression [ 46 ] along with multiple risk factors such as HIV coinfection, tuberculosis, anemia and population age [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%